ANALISIS KESERASIAN BELANJA MODAL DAN BELANJA OPERASIONAL PADA KEUANGAN DAERAH KABUPATEN LOMBOK TIMUR - Siti Sriningsih; Bq Ismiwati; Muhamad Sayuti (Fakultas Ekonomi Universitas Islam Al-Azhar, 2021)
ABSTRACT This study aims to see the compatibility of Capital Expenditures and Operational Expenditures in East Lombok Timur Finance. The type of research is quantitative descriptive research with the Conformity Ratio Analysis Method. The calculation of the ratio shows that it is quite good in terms of the compatibility of Capital Expenditures and the harmony of Operating Expenditures. The good balance shows that the East Lombok Regency Government is able to allocate its regional expenditure to increase development activities in order to achieve targeted growth.